The Role of Zakat in Ensuring Sustainability of Economic Growth and Prosperity Through Decent Work - Abdul Hamid; Jamaluddin (Fakultas Ekonomi dan Bisnis Islam, 2023)
Sustainable Development Goals (SDGs) are a global action plan agreed upon by world leaders, including Indonesia, to end poverty, reduce inequality, and protect the environment by 2030. Eradicating poverty, ending hunger, improving health and education quality are among 17 SDGs. In an Islamic perspective, SDGs are not something new, because Islam already has a zakat instrument for promoting economic welfare and a quality life based on principles of justice. This study aims to empirically measure and analyze the extent to which zakat has played a role in improving the Human Development Index (HDI) in Aceh province. A total of 100 mustahik, who receiving zakat for business working capital distributed by Baitul Mal in Aceh provinces were selected as respondents of the study using purposive sampling technique. Primary data obtained from questionnaires distribution were analyzed using multiple regression technique. Zakat funds for business working capital are believed to have an effective effect on promoting HDI and at the same time support the realization of the achievement of SDGs, particularly the reduction of poverty and hunger, improving the quality of health and education of mustahik. To accelerate the realization of the SDGs, zakat institutions must be managed professionally. The collection of zakat funds to be distributed as working capital for the productive economic activities of the mustahik must be increased.